Comparative analyses of classical phenotypic method and ribosomal RNA gene sequencing for identification of medically relevant Candida species - Taverna, Constanza Giselle (2013)
Instituto Nacional de Enfermedades Infecciosas Dr Carlos G Malbrán. Departamento Micología. Buenos Aires, Argentina.